Features and Function of Woman Language Found in The La La Land Film: A Sociolinguistics Study - Masayu Miranda Balqis; Puspita Sari (Pusat Studi Bahasa dan Publikasi Ilmiah, 2023)
This research aims to examine the features and functions of women's language, according to Lakoff's theory, as demonstrated by the main female character in the film